Basic Concepts and Methodology of Islamic Economics: Foundations of a Fair Economic System Amid Global Injustice - Arum, Hafidza Sanshia; Adel, Ichsanul Reihan; Mahyarni (MUI Kota Pekanbaru, 2025)
This article aims to review the basic concepts and methodologies in Islamic economics as a response to increasing inequality and systemic crises in the modern global economic system. By integrating the bayani, burhani, and irfani approaches, Islamic economics provides an alternative paradigm that is not only normative but also applicable and rational. This article also compares the conventional bank interest system with Islamic finance principles, accompanied by an analysis of the Indonesian government's response to financial access inequality. This study encourages an open approach to the development of Islamic economics rooted in maqasid sharia values and adaptive to innovation. The results of this study show that Islamic economics has great potential to emerge as a fair, sustainable, and relevant economic system in the digital age.